Vesicles From Vibrio cholerae Contain AT-Rich DNA and Shorter mRNAs That Do Not Correlate With Their Protein Products - Langlete, Petter; Krabberød, Anders Kristian; Winther-Larsen, Hanne Cecilie (Frontiers in Microbiology, 2019)
Extracellular vesicles secreted by Gram-negative bacteria have proven to be important in bacterial defense, communication and host–pathogen relationships. They resemble smaller versions of the bacterial mother cell, with similar contents of proteins, LPS, DNA, and RNA. Vesicles can elicit a protective immune response in a range of hosts, and as vaccine candidates, it is of interest to properly characterize their cargo. Genetic sequencing data is already available for vesicles from several bacterial strains, but it is not yet clear how the genetic makeup of vesicles differ from that of their parent cells, and which properties may characterize enriched genetic material. The present study provides evidence for DNA inside vesicles from Vibrio cholerae O395, and key characteristics of their genetic and proteomic content are compared to that of whole cells. DNA analysis reveals enrichment of fragments containing ToxR binding sites, as well as a positive correlation between AT-content and enrichment. Some mRNAs were highly enriched in the vesicle fraction, such as membrane protein genes ompV, ompK, and ompU, DNA-binding protein genes hupA, hupB, ihfB, fis, and ssb, and a negative correlation was found between mRNA enrichment and transcript length, suggesting mRNA inclusion in vesicles may be a size-dependent process. Certain non-coding and functional RNAs were found to be enriched, such as VrrA, GcvB, tmRNA, RNase P, CsrB2, and CsrB3. Mass spectrometry revealed enrichment of outer membrane proteins, known virulence factors, phage components, flagella and extracellular proteins in the vesicle fraction, and a low, negative correlation was found between transcript-, and protein enrichment. This result opposes the hypothesis that a significant degree of protein translation occurs in vesicles after budding. The abundance of viral-, and flagellar proteins in the vesicle fraction underlines the importance of purification during vesicle isolation.